Handbook of Computational Social Science for Policy 2023
DOI: 10.1007/978-3-031-16624-2_24
|View full text |Cite
|
Sign up to set email alerts
|

Towards a More Sustainable Mobility

Abstract: The transport sector is the second most important source of emissions in the EU. It is paramount to act now towards the decarbonisation of our transport system to mitigate climate change effects. Waiting for future technological advancements to minimise the existing anthropogenic emissions and dramatically boost its sustainability is risky for human survival. The current chapter highlights how the path towards a sustainable transport system is a whole stakeholders’ effort involving the mass deployment of avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Regarding the benefits of retrofitting the transportation sector with sustainable solutions, a report by the United Nations Environment Program found that implementing sustainable transport solutions could save up to $70 trillion in infrastructure investments and fuel costs by 2050 while reducing global carbon emissions by up to 90% [45]. Combining green transport technologies, such as hydrogen-powered vehicles, EVs, drones, and electric mobility as a service solution (MaaS), can lead to huge opportunities in fostering the sustainable transition in urban areas [5]. However, these technologies require adequate infrastructure integrated with the built environment, such as charging networks, refuelling stations and landing pads, particularly in large cities.…”
Section: Sustainable Transportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the benefits of retrofitting the transportation sector with sustainable solutions, a report by the United Nations Environment Program found that implementing sustainable transport solutions could save up to $70 trillion in infrastructure investments and fuel costs by 2050 while reducing global carbon emissions by up to 90% [45]. Combining green transport technologies, such as hydrogen-powered vehicles, EVs, drones, and electric mobility as a service solution (MaaS), can lead to huge opportunities in fostering the sustainable transition in urban areas [5]. However, these technologies require adequate infrastructure integrated with the built environment, such as charging networks, refuelling stations and landing pads, particularly in large cities.…”
Section: Sustainable Transportsmentioning
confidence: 99%
“…Therefore, the implementation of energy transition strategies deeply involves the transformation of urban contexts according to high-level guidelines, forming city energy plans, which should establish measurable sustainable targets and specify actions encompassing all technical, economic and social dimensions. This requires a focus on local and urban-level mitigation measures, including the construction of positive energy buildings, deployment of renewable energy systems (RES), promotion of sustainable mobility, creation of resilient urban infrastructure, implementation of circular economy and recycling practices, among others [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%